Perancangan Media Video Company Profile “LPK Logika Internasional” - Robby Annashri; Sandi Justitia Putra (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
To improve service quality, a company must be able to design an informative and persuasive promotional media. LPK Logika Internasional is a company engaged in Japanese language training and courses in the city of Mataram. The problem with this company is a significant decrease in the number of students from year to year. Also, the geographic location that is less strategic makes the company's popularity low so that it affects its existence. This study discusses designing a video company profile at LPK Logika Internasional as useful media information and company promotion. The research method used is the design method (Visual Communication Design), which starts from object/problem analysis, synthesis or data processing, and implementation. The results of this research are in the form of an informative and persuasive, informative and persuasive work of Video Company Profile of the LPK Logika International company. This work expected to be a solution to introduce and promote the company's profile to the fullest.